KINEMATIC ANALYSIS OF FLIGHT IN LONG JUMP AMONG COLLEGE MEN (International Journal of Food and Nutritional Sciences, 2023)
The aim of this study was to make kinematic analysis of flight in long jump among college men. randomly selected ten long jumpers were determined of their long jump performance (LJP) more than six meters in Andhra Pradesh and their kinematic variables, time between heel strike and toe take off (TBS&TO), angle of lead leg knee while take off (ALKTO), time taken to reach the apex from the floor(TRAFF) and time taken to reach apex to floor(TRAF). The long jump performances of the subjects were measured through ‘long jump performance’ and the kinematic variables were measured through video graphical analysis and the measures determined through computer-based software ‘Silicon Coach’